Cover plants and performance of shanks depths under corn productivity - Modolo, Alcir José; Müller, Jônatan; Freitas, Juan Paulo Xavier de; Dotto, Lucas; Dallacort, Rivanildo; Campos, José Ricardo da Rocha; Trogello, Emerson (Ciência e Natura, 2020)
The direct sowing system is characterized by minimum soil rotation and maintenance of vegetal residues in cover. However, incorrect management excessive traffic of machines have caused the emergence of compacted layers, which can cause decrease of crop productivity. The objective of this work was to evaluate the soil parameters and maize crop yield after management with different performance depths of fertilizer shanks, associated to the cultivation of winter coverage plants, in compacted Latosol, conducted in a direct sowing system. The experiment was carried out in two agricultural years (2013/2014 and 2014/2015), in a dystroferric Red Latosol, with a very clayey texture. The experiment was conducted in a randomized complete block design, with treatments arranged in the strip scheme, with two factors and four replications, totaling 32 experimental units. The main treatments were composed by the combination of four performance depths of fertilizer shank (0.065, 0.095, 0.125 and 0.150 m) in the corn sowing process and the secondary ones by the cultivation of two winter coverage plants (black oats and turnip forage). The use of coverage plants and performance depths of the shank, among themselves, did not change the parameters of soil density and porosity, in the intercrop line. The final population of plants, seedling emergence speed index and maize production components did not vary as a result of the performance depth of the shank.